1995
DOI: 10.1007/bf00295914
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery of hepatic hydatid disease: Initial results and early follow‐up of 16 patients

Abstract: Surgery is the main modality in the treatment of hepatic hydatid disease. In this report, a laparoscopic surgical method is described, and the results in the first 16 cases are presented. The method involves the use of an aspirator-grinder apparatus that achieves effective evacuation of viable cyst contents with the patient benefiting from the laparoscopic approach. Cavity infection occurred in two patients and was treated conservatively. In another patient, postoperative ultrasonography revealed a thick-walle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
1
6

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 16 publications
0
51
1
6
Order By: Relevance
“…Thick and calcified wall cysts should not be treated laparoscopically because of the possible problems in obliterating the residual cavity. It is reported that in such patients laparoscopic treatment entails higher morbidity and recurrence rates [8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thick and calcified wall cysts should not be treated laparoscopically because of the possible problems in obliterating the residual cavity. It is reported that in such patients laparoscopic treatment entails higher morbidity and recurrence rates [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore the surgeon should be very fastidious during the operation. Filling the subdiaphragmatic space with povidone iodine (in right lobe cysts), filling the cyst with 20% hypertonic saline solution and waiting for 5 min [8, 9] and using two aspirators reduce the risk of spreading. It is very hard to evacuate the cyst without spreading.…”
Section: Discussionmentioning
confidence: 99%
“…(24) In classical open surgery, overall postoperative mortality ranges between 0% (25) to as high as 7.5% (26) in the early period. Morbidity is also observed in 4-25% (13,16,18) of the cases. It is better and safe to use laparoscopic surgery in treatment of hydatid liver with less morbidity, mortality, and shorter hospital stay and recurrence rate in comparison with open technique.…”
Section: Discussionmentioning
confidence: 95%
“…Hasta el momento hay 16 trabajos publicados [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] con casuísticas superiores a los 20 casos (Tabla 10), el resto de las publicaciones presenta series menores a esta cifra. El total de pacientes alcanza a los 791, y en base a estas cifras se evalúan nuestros resultados.…”
Section: Discussionunclassified